(untitled) (Journal of the College of Basic Education, 2022)
The current study aimed at the effect of an extract of chromium alanine from Fusornmar, the local green apple plant Pyrus malus, on the growth of three bacterial isolates, two isolates of Gram-negative bacteria (Proteus vulgaris Escherichia (coli) and an isolate of positive bacteria Gram stained (Staphyllococcus aureus). The results of the inhibitory activity of the peel and alcoholic pulp extracts by means of tablets showed a difference in their effect towards the bacteria included in the study, as the alcoholic peel extract had more inhibitory effectiveness compared to the alcoholic pulp extract, and the bacterium wulgaris ... was the most affected by the peel extract, where the diameter of the inhibition zone was (2,2,2, 1.5.0.9) cm at concentrations (40, 200, 100, 400)